The association between human resource management and organisational performance: a literature review - Pombo, Gonçalo (2022)
This paper reviews the literature on the relationship between human resource management (HRM) and organisational performance (OP), and offers some insights ranging from the ability-motivation-opportunity framework and the social processing theory, through to the advance theory on the HRM-OP linkage. The text highlights how individual factors such as individual perceptions and interpretations influence outcomes. Furthermore, it argues that even though the design and conception of well-designed HR policies and processes are important, the application and implementation of such policies and processes by managers also exert a powerful influence on performance. In fact, management leadership can play a crucial role by distorting, reinforcing, or stimulating how employees perceive and interpret HR policies and the whole HRM-OP linkage. This study ends by offering important insights regarding the linkages between the HRM system and direct and middle managers on the one hand, and between these managers and employees on the other hand.